Can trifluoperazine protect mitochondria against reactive oxygen species-induced damage? - De Souza Pereira, R. [UNESP]; Hermes-Lima, M. (Springer Nature, 1996)
Trifluoperazine (TFP) (35 μM) prevents mitochondrial transmembrane potential (ΔΨ) collapse and swelling induced by 10 μM Ca2+ plus oxyradicals generated from δ-aminolevulinic acid autoxidation. In contrast with EGTA, TFP cannot restore the totally collapsed ΔΨ. So, TFP might not remove Ca2+ from its 'harmful site', but could impair the ROS-driven cross-linking between membrane -SH proteins. Our data are correlated with the protective uses of TFP against oxidative processes promoted by oxyradicals plus Ca2+.
Keywords: Ca2+; Mitochondria; Oxidative stress; Reactive oxygen species; Trifluoperazine; reactive oxygen metabolite; trifluoperazine; animal tissue; liver disease; liver mitochondrion; membrane potential; mitochondrial membrane; mitochondrion swelling; nonhuman; oxidative stress; rat; Aminolevulinic Acid; Animals; Calcium; Membrane Potentials; Mitochondria, Liver; Oxidation-Reduction; Permeability; Rats; Rats, Wistar; Reactive Oxygen Species